2011
DOI: 10.1007/s10705-011-9424-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term tillage, straw management and N fertilization effects on quantity and quality of organic C and N in a Black Chernozem soil

Abstract: Soil, crop and fertilizer management practices may affect the amount and quality of organic C and N in soil. A long-term field experiment (growing barley, wheat, or canola) was conducted on a Black Chernozem (Albic Argicryoll) loam at Ellerslie, Alberta, Canada, to determine the influence of 19 (1980 to 1998) or 27 years (1980 to 2006) of tillage (zero tillage [ZT] and conventional tillage [CT]), straw management (straw removed [S Rem ]and straw retained [S Ret ]) and N fertilizer rate (0, 50 and 100 kg N ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
35
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 49 publications
9
35
1
1
Order By: Relevance
“…Inorganic amendments usually supply specific nutrients and do not contribute directly to soil organic matter, resulting in much less contribution to soil organic C and N. Other recent research in Germany has also shown significant increase in soil organic matter after four annual applications of farm yard manure (FYM) to organic crops [7]. The relative greater increases in C or N for LFOC or LFON than TOC or TON in our study are in agreement with other research, where light organic fraction was also more responsive to management practices than total organic fraction [14][15][16]. The greater build-up of light organic fraction at Star City than Spalding was probably due to the differences in soil type (Gray Luvisol soil at Star City versus Dark brown Chernozem at Spalding) and climatic conditions (relatively warmer temperature at Spalding than Star City) at the two sites.…”
Section: Soil Organic C and Nsupporting
confidence: 92%
See 1 more Smart Citation
“…Inorganic amendments usually supply specific nutrients and do not contribute directly to soil organic matter, resulting in much less contribution to soil organic C and N. Other recent research in Germany has also shown significant increase in soil organic matter after four annual applications of farm yard manure (FYM) to organic crops [7]. The relative greater increases in C or N for LFOC or LFON than TOC or TON in our study are in agreement with other research, where light organic fraction was also more responsive to management practices than total organic fraction [14][15][16]. The greater build-up of light organic fraction at Star City than Spalding was probably due to the differences in soil type (Gray Luvisol soil at Star City versus Dark brown Chernozem at Spalding) and climatic conditions (relatively warmer temperature at Spalding than Star City) at the two sites.…”
Section: Soil Organic C and Nsupporting
confidence: 92%
“…Soil quality is linked to organic matter (or organic C) in soil, and the increase of organic C in soil is a function of the amount of C input to soil and its balance with decomposition [14][15][16]. Thus, organic amendments (because of both direct and indirect C input) can have much greater residual benefits in improving soil organic matter/quality and fertility compared to inorganic amendments which contribute only indirectly to C input in soil [3][4][5][6][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the chelating of these nutrients with organic matter in non-disturbed soil leads the improvement of soil nutrient status in different soil depths (Borie et al, 2006;Singh et al, 2014) and thus causes enhancement of soil NPK status. The similar findings of enhancement in available nutrients due to CA practices in soil were also reported by Graham et al, 2002;Borie et al, 2006 andWang et al, 2008 for N;Malhi et al, 2011for P and Du Preez et al, 2001and Govaerts et al, 2007 for K. The enhancement in available NPK status due to ZT and PB practices was also reported by Parihar et al, 2011. Most research reported that tillage practices does not affect extractable Ca and Mg levels of soil (Govaerts et al, 2007;Duiker and Beegle, 2006) primerily in the condition where CEC is associated with clay particles (Duiker and Beegle, 2006).…”
Section: Nutrient Dynamicssupporting
confidence: 79%
“…Hence, the essence of efficient water use was root and shoot equilibrium (Gao et al 2007). Straw mulching affects not only the soil moisture content but also soil temperature and soil nutrient accumulation and distribution (Yan et al 2007, Li et al 2008, Malhi et al 2011. Therefore, to understand the water consumption characteristics of summer maize with straw mulching more clearly, the regulation and control mechanisms of root and shoot equilibrium, as well as its interaction mechanisms under different soil and water conditions should be studied.…”
Section: Resultsmentioning
confidence: 99%